A4_16 Set Phasers to stun - Conlon, Thomas; Coxon, John; Barker, Joshua (Physics Special Topics, 2011)
This article considers the possibility of creating a ’stun ray’ style weapon similar in concept to the phaser used in Star Trek when on a setting to stun its target. It is found that in order to create such an energy based stun weapon which was effective over a similar range to that of the phaser which did not simply kill the target should be technologically possible.